2023
DOI: 10.3390/molecules28186660
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Antioxidant Potential of Phenolic Compounds from Winery By-Products by Hydroethanolic Extraction

Rui Dias Costa,
Raúl Domínguez-Perles,
Ana Abraão
et al.

Abstract: The residues generated in the wine industry (pomace, stems, seeds, wine lees, and grapevine shoots) are a potential source of bioactive compounds that can be used in other industries despite being sometimes underestimated. Different extraction methods using various solvents and extraction conditions are currently being investigated. Due to its natural occurrence in wines, safe behavior, and low toxicity when compared to other organic solvents, ethanol is used as an extracting agent. The aim of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Our results also have shown ( Table 1 ) that the yield of the phenolic compounds was not increased, and even had a tendency to be lower when β-cyclodextrin (5%) was used as an excipient during the hydroalcoholic extraction of polyphenols from A. annua and A. vulgaris . Other studies have shown that the efficiency of β-cyclodextrin in extracting a broad spectrum of phenolic compounds may not be equal to that of more traditional solvents [ 35 , 36 ]. Hydroalcoholic solutions, without the addition of cyclodextrins, can often extract a wider range of phenolics more efficiently due to their ability to dissolve both hydrophilic and hydrophobic compounds [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also have shown ( Table 1 ) that the yield of the phenolic compounds was not increased, and even had a tendency to be lower when β-cyclodextrin (5%) was used as an excipient during the hydroalcoholic extraction of polyphenols from A. annua and A. vulgaris . Other studies have shown that the efficiency of β-cyclodextrin in extracting a broad spectrum of phenolic compounds may not be equal to that of more traditional solvents [ 35 , 36 ]. Hydroalcoholic solutions, without the addition of cyclodextrins, can often extract a wider range of phenolics more efficiently due to their ability to dissolve both hydrophilic and hydrophobic compounds [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the efficiency of β-cyclodextrin in extracting a broad spectrum of phenolic compounds may not be equal to that of more traditional solvents [ 35 , 36 ]. Hydroalcoholic solutions, without the addition of cyclodextrins, can often extract a wider range of phenolics more efficiently due to their ability to dissolve both hydrophilic and hydrophobic compounds [ 35 , 36 ]. The use of titanium dioxide as an excipient in food and pharmaceutical products has been subject recently to regulatory scrutiny due to concerns over its safety, especially in nanoparticle form [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because antioxidant activity is by far the most important characteristic of plant extracts, the main determinations are focused on the identi cation and dosage of phenolic compounds (Abdelwahab et ( Sari et al, 2023) or statistical analysis (Costa et al, 2023).…”
Section: Introductionmentioning
confidence: 99%